(untitled) (Historia, 2021)
Jan Christiaan Smuts -born on May 24, 1870 of a simple country family on the farm Bovenplaats, near Riebeek West in the Cape Province-grew to so great a stature that in truth for him, was all the world a stage. There was no South African in the modern sense -just the two impoverished republics of the Transvaal and the Orange Free State;. only the Cape was prosperous and, even there, economic security was threatened by the opening of the Suez Canal and the consequent re-routing of shipping. Smuts lived to serve as soldier and statesman in the years which saw one old, comfortable world die and another new, dangerous, exciting world come to birth. In the years 1900-1950, the first half of the 20th centurry, Smuts emerged time and time again from the lofty mountains and broad veld of his beloved South Africa, to "walk with Kings", to give guidance to the world’s great leaders, to suffer with the common man and to inspire those ideals of united purpose and world government which are yet to be.